Adaptation of Manufacturing Machines by the Use of Multiple-Domain-Matrices and Variability Models. Issue 13 (2019) - Hoang, Xuan-Luu; Caesar, Birte; Fay, Alexander
Abstract: Global trends in manufacturing oblige companies to become more adaptable, as the production environment becomes increasingly dynamic. Here, companies have to cope with frequent changes of production requirements and conditions. In order to handle these changes, manufacturing machines have been designed to be reconfigurable. However, to efficiently utilize the available configurations of manufacturing machines, information regarding interdependencies between requirements and resource configurations are needed. Such an information model should enable an efficient usage of available machine configurations and also support the creation of new configurations, if needed. Accordingly, in this contribution, an approach is presented that combines two different modelling concepts. Here, Multiple-Domain-Matrices are used to model interdependencies between production requests and machine configurations and to generate adaptation options. In addition, context-sensitive feature models are utilized to describe the available configurations of the machine. The applicability of the approach is illustrated by an example of a drilling module.